Mechanical properties of cellulose fibres and wood. Orientational aspects in situ investigated with synchrotron radiation - Kölln, Klaas (Journal of synchrotron radiation, 2005)
Highly oriented native cellulose fibres (flax) and softwood (pine) have been investigated by means of X-ray diffraction. Local structural information was obtained by using X-ray microbeams. Tensile tests were performed in situ, revealing a change of orientation of cellulose microfibrils in materials with tensile strain. In flax fibres, the microfibrils rotate during the first percent of stretching, into a more parallel orientation with respect to the fibre axis. For wood, a decrease of orientation with the onset of strain hardening is found for the first time